Cladosporium cladosporioides and Cladosporium pseudocladosporioides as potential new fungal antagonists of Puccinia horiana Henn., the causal agent of chrysanthemum white rust. - David Eduardo Torres; Reyna Isabel Rojas-Martínez; Emma Zavaleta-Mejía; Patricia Guevara-Fefer; G Judith Márquez-Guzmán; Carolina Pérez-Martínez (PLoS ONE)
Puccinia horiana Hennings, the causal agent of chrysanthemum white rust, is a worldwide quarantine organism and one of the most important fungal pathogens of Chrysanthemum × morifolium cultivars, which are used for cut flowers and as potted plants in commercial production regions of the world. It was previously reported to be controlled by Lecanicillium lecanii, Cladosporium sphaerospermum, C. uredinicola and Aphanocladium album, due to their antagonistic and hyperparasitic effects. We report novel antagonist species on Puccinia horiana. Fungi isolated from rust pustules in a commercial greenhouse from Villa Guerrero, México, were identified as Cladosporium cladosporioides and Cladosporium pseudocladosporioides based upon molecular analysis and morphological characters. The antagonism of C. cladosporioides and C. pseudocladosporioides on chrysanthemum white rust was studied using light and electron microscopy in vitro at the host/parasite interface. Cladosporium cladosporioides and C. pseudocladosporioides grew towards the white rust teliospores and colonized the sporogenous cells, but no direct penetration of teliospores was observed; however, the structure and cytoplasm of teliospores were altered. The two Cladosporium spp. were able to grow on media containing laminarin, but not when chitin was used as the sole carbon source; these results suggest that they are able to produce glucanases. Results from the study indicate that both Cladosporium species had potential as biological control agents of chrysanthemum white rust.